Mathematical models of the spread of dengue fever in Shah Alam / Nuraini Yusoff - Yusoff, Nuraini (Institute of Graduate Studies, UiTM, 2015)
Dengue fever has been a serious health threat in Malaysia and more than 50 other countries which are located in tropical and subtropical regions. It is a vector-borne disease and its main vector is the Aedes aegypti mosquito. Understanding the spread of this disease will certainly help in controlling it and this can be done with the help of mathematical models. In order to come up with a suitable model, an in depth study on the role of temperature and amount of rainfall in contributing to the number of dengue fever cases was done. In this study, two main parts of modeling were done, one was the modeling of the population dynamics of the vector, and another was on the modeling of the epidemic. In the modeling of the Aedes aegypti mosquito, a stagestructured model was constructed based on the temperature and rainfall of Shah Alam. A simulation was done and verified with the surveillance data collected by Majlis Bandaraya Shah Alam. The result obtained was tabulated and represented as a cosine function. For the epidemic model, the vector population was divided into two stages, before and after first egg-laying. This was done because it was found that the biting rates for these two groups of vectors vary and affect the modeling result. Result from the modeling of Aedes aegypti mosquitoes was used as the recruitment rate for vectors in the construction of the vector-host epidemic model…